Conceptual metaphors in the French discourse (Eurasian Journal of Philology Science and Education, 2020)
Innovation in linguistics, replacing one paradigme with another, lead to new research methods. In recent years, the place of language in society as well as the role of the language, the reflection and expression of the surrounding world, the study of the mental aspects of the concept of reality have been one of the main linguistic objects, which has led to the formation of cognitive language. Cognitive-discursive nature of modern linguistics are considered the most promising because it is it allows extremely new, sometimes unexpected results for understanding the world and man, and interpreting language manifestations in a new way. In modern linguistics, the concept of discourse is one of the most commonly used, but at the same time it does not have a clear definition. Science presents two points of view on the essence of discourse. The first point of view is associated with human social activity. According to the second point of view, the linguistic personality becomes part of discursive research. The study of political communication in the current international situation is in the focus of the interests of many sciences, including psycholinguistics. The article is devoted to the study of modern political discourse in French language as a specific form of communication. The general approaches to the phenomenon of discourse in modern linguistics are covered. The peculiarities of nominative metaphors used for naming political events participants and their potential for speech impact are investigated. The author stresses the fact that the correctly chosen method of speech influence can significantly affect the political views of the addressee. The dominant role of the factor of noninstitutionality, informativeness, emotionality and semantic uncertainty of the political discourse is emphasized by the functioning of political metaphors reflecting the specific characteristics of the object and having a psychological effect on the recipient.